Long term effect of latanoprost on intraocular pressure in normal tension glaucoma. Issue 5 (16th April 2004) - Ang, A; Reddy, M A; Shepstone, L; Broadway, D C
Abstract : Aim: To determine the long term effect of latanoprost on the intraocular pressure (IOP) of patients with normal tension glaucoma (NTG). Methods: Newly diagnosed patients with NTG were recruited into the study and had their baseline IOPs measured hourly between 8 am and 5 pm using a handheld electronic Tonopen. Patients with fixation threatening field defects were placed immediately into the treatment group while those with non-fixation threatening field defects were randomised into either the treatment group or the control group (no treatment). Treatment consisted of once daily topical latanoprost 0.005%. After a minimum period of 6 months, the patients underwent a second period of IOP phasing. Results: 76 newly diagnosed patients with NTG were recruited—26 had fixation threatening disease, 25 were randomised to treatment, and 25 randomised to the control group. The average duration of treatment was 11 months. The average and maximum diurnal IOP for the patients randomised to treatment were statistically significantly lower than for the control patients at follow up (p<0.05). The treated group as a whole demonstrated a 17% decrease in the average diurnal IOP and a 19% decrease in the maximum diurnal IOP when compared to baseline IOP. 41% of those treated achieved a decrease of at least 20%, but only 10% of patients achieved a decrease of at least 30%. Conclusion: Latanoprost had a sustained hypotensive effect in eyes with NTG and 41% of treated patients achieved a reasonable response. However, in the majority of eyes with NTG, latanoprost monotherapy may be insufficient in producing a desirable 30% reduction in IOP.